Quick comments from participants in the Third Multi-Stakeholder Platform Meeting of The Global Agenda of Action in Support of Sustainable Livestock Sector Development, Nairobi, 22-24 January 2013 - International Livestock Research Institute (International Livestock Research Institute, 2013)
Nearly 100 participants from over 20 countries took part in the Third Multi-Stakeholder Platform Meeting of the Global Agenda of Action in Support of Sustainable Livestock Sector Development co-hosted in Nairobi, Kenya by ILRI, FAO and AU-IBAR, 22-24 January 2013.